(De)Construction of Trans* Parenthood: Pregnant Men (ex æquo, 2023)
(De)Construction of Trans Parenthood: Pregnant MenGetting pregnant and having children is a reality for some trans men who resist the construction of pregnancy associated with cisgender women. However, forms of discrimination, especially in healthcare, result in the avoidance of these services and have an impact on individual health of the trans person and the baby. To deal with the visibility of pregnancy, a set of strategies are adopted but none of them protects these people. In this sense, this theoretical review intends to reflect on the oppression perpetuated by the cisnormative culture that affects trans pregnant men, alerting to the need of thinking about these experiences and creating conditions that contemplate the diversity and well-being of all people.
Keywords: trans pregnant men, rights, reproduction, parenthood; Trans* pregnant men, rights, reproduction, parenthood